Environmental education and formation of teachers as ecological persons: processes of human development, empowerment and emancipation - Campos, Daniela Bertolucci [UNESP]; Feiteiro Cavalari, Rosa Maria [UNESP] (Federal Univ Rio Grande, Inst Education, 2017)
For a critical and emancipatory Environmental Education it is necessary to prepare teachers who act as ecological persons, in other words, possible environmental educators in the formal context. This formation, initial and / or continued, must transcend the programmatic objectives of undergraduate courses and continuing teacher training to work the formation of a personal and professional identity, linked to environmental issues. Based on results obtained in previous studies, review and reflection of the literature on the theme, we will discuss this identity formation towards the constitution of ecological persons which is related to education processes as human development, empowerment and emancipation.
Keywords: Critical Environmental Education; Teacher training; Empowerment